'Fixing my life': young people's everyday efforts towards recovery from persistent bodily complaints. Issue 4 (1st October 2020) - Kvamme, Maria Fredriksen; Wang, Catharina Elisabeth Arfwedson; Waage, Trond; Risør, Mette Bech
Abstract: Little is known about the perspectives of young people suffering from medically unexplained symptoms. This study aims to explore the experiences and strategies of young Norwegians related to incipient and persistent health complaints affecting everyday life functioning. The study draws on field notes, video material and interview transcripts from a multi-sited ethnographic study of healthcare services and select schools in a small Norwegian town between 2015 and 2016. A central theme is the emphasis upon social and existential constraints seemingly framed by a social imaginary of youth rather than a medical imaginary, and their active engagements to 'fix' their lives through what we identify as two main modalities of self-care. Navigating temporal and relational aspects of sociocultural configurations of youth in their social environments, they imagine and enact alternative qualifying positions better adapted to constraints, personal preferences and needs. Our findings may add to understandings of the needs and strategies of young sufferers of medically unexplained symptoms, relevant for health and social care encounters.